Хмонг мəдениетінің демонологиясы. Демонология в культуре хмонгов. - Saikeneva, D. K. (Journal of Oriental Studies, 2016)
Demonology in hmong minority’s culture In this article author considers presence of mythology in the modern life of traditional society, and transformation of archaic fears to modern phobias. The article represents analysis of night mare’s archetype in Hmong’s culture. Author considers necessity of reconstruction traditional society’s mythology, which give understanding of habits and thinking of traditional groups. This example covers post-war situation in the U.S.A. There are representatives of Hmong’s minority faced with revival of primal fear before night mare in their consciousness. In conclusion, the author infers need for integrated study of mythology, for a more adequate interpretation of the changes in the life of traditional societies. Thus, in the article, the author focuses on the reconstruction of the mythology, uses typological parallels from other traditional myths and traditional beliefs, which helps to establish the spatial, social and cultural characteristics of traditionsand transformationof the archetypes in the world. The author contributes to the understanding of the role of tradition in modern Hmong culture.